Ocular biometry and anthropometric measurements in young myopes – A case–control study - Venipriya Sigamani; Viswesh Kathavarayan; Lalithambigai Chellamuthu; Ravichandran Kandasamy; Hannah Ranjee Prasanth (Asian Journal of Medical Sciences, 2024)
Background: The prevalence of myopia in the 5–15-year age group in India has been 7.5% over the past four decades. While ocular growth and physical growth occur simultaneously during early life, the existence of a common regulatory system for both is still debated. Aims and Objectives: This study aims to analyze the ocular biometry and anthropometric values of young myopes and emmetropes aged 18–25 years. Materials and Methods: This case–control study involved a sample size of 86 participants. Corneal curvature was measured using keratometry, while A-scan ultrasonography was utilized to measure axial length, lens thickness, anterior chamber depth, and vitreous chamber depth. Results: The results indicated that there were no significant differences in ocular biometry and anthropometric values between the case and control groups, except for corneal thickness and axial length. The mean corneal thickness was found to be 549.64 μm in the case group and 566.05 μm in the control group, while the mean axial length was 24.70 mm in the case group and 23.41 mm in the control group. An increase in height was correlated with longer axial length in myopes. Conclusion: There was no difference in anthropometry and ocular biometry in emmetropes and myopes in the age group of 18–25 years of age. Myopes tend to have thinner corneas, which should be taken into consideration before performing refractive surgeries. The presence of thin corneas in individuals with myopia can result in inaccurately low measurements of intraocular pressure, potentially hampering the early detection of glaucoma within this high-risk demographic.